2005
DOI: 10.1111/j.1469-7580.2005.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular proliferation in the urorectal septation complex of the human embryo at Carnegie stages 13–18: a nuclear area‐based morphometric analysis

Abstract: In order to analyse the patterns of cellular proliferation both in the mesenchyme of the urorectal septum (URS) and in the adjacent territories (posterior urogenital mesenchyme, anterior intestinal mesenchyme and cloacal folds mesenchyme), as well as their contribution to the process of cloacal division, a computer-assisted method was used to obtain the nuclear area of 3874 mesenchymal cells from camera lucida drawings of nuclear contours of selected sections of human embryos [Carnegie stages (CSs) 13-18]. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Cell replication rates in the cloacal wall and its surrounding mesenchyme appear similar in human (Nebot‐Cegarra et al. ) and mouse embryos (Matsumaru et al. ), but rapid proliferation may continue longer in mesenchyme than epithelium (Matsumaru et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cell replication rates in the cloacal wall and its surrounding mesenchyme appear similar in human (Nebot‐Cegarra et al. ) and mouse embryos (Matsumaru et al. ), but rapid proliferation may continue longer in mesenchyme than epithelium (Matsumaru et al.…”
Section: Discussionmentioning
confidence: 98%
“…Cell replication rates in the cloacal wall and its surrounding mesenchyme appear similar in human (Nebot-Cegarra et al 2005) and mouse embryos (Matsumaru et al 2015), but rapid proliferation may continue longer in mesenchyme than epithelium (Matsumaru et al 2015). Observed regional differences in growth, therefore, point to regional accumulation of extracellular matrix or regional differences in cell death.…”
Section: Fate Of the Cloacamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also revealed an endodermal origin of the perineum, which is the first demonstration that endoderm differentiates into skin (4). Disturbances in spatial and sequential proliferation control and septal displacement of the urorectal septum by adjacent mesenchyme might be responsible for this type of mild malformation (5). Perineal groove might be associated with other regional anomalies like perineal ectopic anus or penoscrotal hypospadia (6).…”
Section: Discussionmentioning
confidence: 99%
“…The cloaca is usually shown as a midsagittal drawing, with histological sections to support developmental processes in other planes. In addition, the growth pattern in the cloacal region has been globally described (van der Putte, 2004), with most quantitative histological data addressing cell proliferation and apoptosis (Sasaki et al, 2004, Nebot-Cegarra et al, 2005, Matsumaru et al, 2015, Huang et al, 2016. To clarify the growth pattern and the fate of the components of the cloacal region, we reinvestigated the changes in shape of the cloaca, including its lumen, wall, and surrounding mesenchyme in human embryos and foetuses between 4 and 10 weeks of development.…”
Section: Introductionmentioning
confidence: 99%